A chicken's guide to talking turkey with your kids about sex - Leman, Kevin; Bell, Kathy Flores, 1958- (Grand Rapids, Mich. : Zondervan, 2004)
Provides a guide for talking to children about sex before they reach adolescence, and includes real-life scenarios, practical knowledge, and biblical wisdom, and examines such things as dating, sexual activity, sexually transmitted diseases, and molestation.
Includes bibliographical references (p. 201-203) and index.
Keywords: Sex instruction; Puberty; Sexual ethics; Parenting